2016
DOI: 10.1039/c5cp05778g
|View full text |Cite|
|
Sign up to set email alerts
|

The thermodynamics of endosomal escape and DNA release from lipoplexes

Abstract: Complexes of cationic and neutral lipids and DNA (lipoplexes) are emerging as promising vectors for gene therapy applications. Their appeal stems from their non pathogenic nature and the fact that they self-assemble under conditions of thermal equilibrium. Lipoplex adhesion to the cell plasma membrane initiates a three-stage process termed transfection, consisting of (i) endocytosis, (ii) lipoplex breakdown, and (iii) DNA release followed by gene expression. As successful transfection requires lipoplex degrada… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“… 127 , 128 The thermodynamic stability of lipoplexes is greatly influenced by their phase structure; that is, the lamellar phase is considered to be more thermodynamically stable than the hexagonal phase, which requires lower energy to trigger membrane fusion. 125 In addition, the lamellar complex needs complete fragmentation to release DNA, while the hexagonal complex can release DNA even if it is not completely disintegrated. 127 Therefore, an excellent gene delivery vector should be capable of phase transition to meet the requirements of effective drug delivery and drug dissociation.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“… 127 , 128 The thermodynamic stability of lipoplexes is greatly influenced by their phase structure; that is, the lamellar phase is considered to be more thermodynamically stable than the hexagonal phase, which requires lower energy to trigger membrane fusion. 125 In addition, the lamellar complex needs complete fragmentation to release DNA, while the hexagonal complex can release DNA even if it is not completely disintegrated. 127 Therefore, an excellent gene delivery vector should be capable of phase transition to meet the requirements of effective drug delivery and drug dissociation.…”
Section: Main Textmentioning
confidence: 99%
“…121,122 Endosomal escape, which relies on membrane fusion, is an indispensable step for lipoplexes trapped in endosomes to acquire satisfactory nucleic acid therapeutic outcome, as it is generally accompanied by drug release. [123][124][125] The positive charge of the lipoplex attracts the anionic lipids of the endosomal membrane to flip-flop from the outer face to the inner face and diffuse into the lipoplex, forming a neutral ion pair with cationic lipids and resulting in displacement of DNA from the lipoplex as well as endosomal disruption. 124 During the same time, the nucleic acid can be released into the cytoplasm when the total cationic charge of the lipoplex is completely neutralized by the endosomal membrane.…”
Section: Endosomal Escape and Drug Releasementioning
confidence: 99%
“…Improving cellular uptake is the most common approach to enhance siRNA delivery efficiency, such as increasing the electrostatic interaction between nonviral vectors and negatively charged cytoplasmic membranes , and adopting receptor-mediated endocytosis. However, with the further understanding of siRNA delivery, intracellular release is believed to be the critical step to enhance siRNA delivery efficiency. Several studies have demonstrated that the vast majority of internalized siRNAs are considered to be trapped into late endosomes and lysosomes and only a small fraction of siRNA is released into the cytoplasm to come into play regardless of the release mechanism. Even for a most advanced nonviral siRNA in clinical application, only ∼3.5% or 1–2% internalized siRNAs can escape from endosome and be released into the cytosol. , It is considered that only <2000 copies of cytosolic siRNAs/cell is needed to cause maximal knockdown of targeted gene, , while highly exceeded doses of siRNA are needed by nonviral vectors to get a certain transfection efficiency due to the low delivery efficiency. , As reported, the opportunity for siRNA release only occurred in maturing endosomes within a narrow time window of 5–15 min after uptake . To date, a common hypothesis for enhancing endosomal release is to use vectors with appropriate p K a that could respond to the microenvironment of endosomes and then burst to release siRNA, which is referred as proton sponge. , Besides, other factors may contribute to the endosomal escape and have also been widely studied, such as the advanced “programmed packaging” concept, the thermodynamics of endosomal escape, and so on. Considering the minor pH difference (within 0.5 pH unit) between the early endosome and the late endosome, developing pH-sensitive vectors with defined structures that could respond and escape from early endosome should be an ideal solution to facilitate endosomal releasing. The pH-sensitive polycations, loading siRNA via electrostatic interaction, could respond to microenvironment of cells and thus be widely used on siRNA delivery materials. , Nowadays, advanced pH-sensitive vectors have been designed by combining several improvement components including the ultra pH-sensitive inner core to enhance endosome release for high-efficiency siRNA delivery .…”
mentioning
confidence: 99%
“…Here, the positive charge of the NPs plays a pivotal role when it attracts the anionic lipids of the endosomal membrane. The total cationic charge neutralizes the total anionic endosomal membrane and results in nucleic acid release from the endosomal complex (Avital et al, 2016). However, the nucleic acid dissociation from the endosomal/nanoparticle complex is not easy because various factors, such as thermodynamic stability, membrane charge destiny, and so forth, influence the cargo release (Figure 2) (Ahmad et al, 2005; Pozzi et al, 2009).…”
Section: An Overview Of Pbae Synthesismentioning
confidence: 99%